The Effect of the Transmission Impact of the U.S Interest Rate on Turkey’s CO2 Emissions: Evidence from Bootstrap ARDL - Samour, Ahmed; Isiksal, Aliya Zhakanova; Tursoy, Turgut (Indonesian Journal of Sustainability Accounting and Management, 2021)
The U.S. economy is the largest in the world; any change in the US economic policies exert a significant impact on global markets. The main purpose of this study is to investigate the spillover effect of the U.S interest rate on Turkey’s CO2 emission. The empirical results and the subsequent study discussion will be the first contribution of its kind to the environmental literature field. The study employs the newly developed bootstrap autoregressive distributed lag (ARDL) testing approach as proposed by McNown et al. (2018). The main findings of this study show that there is a negative and significant relationship between the U.S interest rate and Turkey’s CO2 emission. The results also provide significant evidence of the spillover effects of the U.S interest rate on CO2 emission in Turkey through the domestic interest rate, economic growth, and energy consumption channels. It is suggested that policymakers should design strategies such as sustained economic growth for responding to any external shocks, in particular, the U.S interest rate.